2019
DOI: 10.1136/tobaccocontrol-2018-054811
|View full text |Cite
|
Sign up to set email alerts
|

Financial incentives to Medicaid smokers for engaging tobacco quit line treatment: maximising return on investment

Abstract: BackgroundLow-income smokers experience greater difficulty in quitting smoking than do other smokers. Providing financial incentives for treatment engagement increases smoking cessation success. This study models the cost-effectiveness of varying levels of financial incentives to maximise return on investment (ROI) for engaging low-income Medicaid recipients who smoke to take calls from a tobacco quit line.MethodsParticipants (N=1900) were recruited from May 2013 to June 2015 through quit line-based (n=980), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“… 12 Emerging evidence suggested the use of modest incentives (US$60–US$190) contingent upon treatment use 18 , 19 and small amount of monetary incentives are more sustainable for application in large community-based smoking cessation programs. 20 Our previous trial found a small, abstinence-contingent incentive (HK$500/US$64) effective in increasing quit attempt, but the effects on service use and abstinence was inconclusive. 17 By different design features, incentives of similar amount varied in type, frequency, condition, and delivery of payment produced various effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Emerging evidence suggested the use of modest incentives (US$60–US$190) contingent upon treatment use 18 , 19 and small amount of monetary incentives are more sustainable for application in large community-based smoking cessation programs. 20 Our previous trial found a small, abstinence-contingent incentive (HK$500/US$64) effective in increasing quit attempt, but the effects on service use and abstinence was inconclusive. 17 By different design features, incentives of similar amount varied in type, frequency, condition, and delivery of payment produced various effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of financial incentives, its efficacy is presented in decreasing the severity of withdrawal symptoms [ 37 ] in time no longer than one-year post-intervention [ 47 ]. Video-based interventions such as those conducted by Bloom et al [ 50 ] QuitBet platform, and Scholten et al [ 49 ] with the go/no-go training game for smoking cessation in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, denying smokers with high SES an effective treatment might be seen as discrimination. Financial incentives are not only an evidence-based and highly effective smoking cessation method, but the strategy also seems to be highly cost-effective (a good investment) [ 39 , 40 , 41 , 42 ]. Therefore, one could argue that it should be offered to as many smokers as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that neither the FIMs nor the CAMs succeeded in attracting more smokers with low SES during the intervention year than the year before. Previous studies indicated that financial incentives can be a good recruitment method to smoking cessation activities [ 43 , 44 ], even for disadvantaged smokers [ 39 ]. Evidence on interventions that are successful in attracting smokers with low SES to smoking cessation services is needed.…”
Section: Discussionmentioning
confidence: 99%